Comparison of nystatin and fluconazole effects in the healing of oral candidiasis in immunocompromised individuals - Stepovic, Milos; Stajic, Dalibor; Sekulic, Marija; Maricic, Milena; Djonovic, Nela (Medicinski časopis, 2019)
Oral candidiasis is a common fungal infection of the mouth in immunocompromised individuals. It occurs when it meets ideal conditions for breeding and represents an obstacle to patients. Candida treatment consists of solving the contributing factors and in addition application of certain antifungal drugs, including nystatin and fluconazole. Evaluation of the efficacy of these drugs is important in narrowing the choice of drugs in the selection therapy. The purpose of this study was to compare the efficacy of nystatin and fluconazole in the treatment of candida albicans. For this study two databases were searched: PubMed and SCIndex - in order to find papers that are appropriate in their content in making the conclusion which meet the criteria of validity and significance. In search of papers were used different combinations of keywords based on the obtained studies that have been dealt with comparing one of these two antifungal drugs. After analysing all of these studies, a number of studies that have fulfilled the criteria of validity and significance has been reduced to 8. Results of comapared studies have shown that the advantage in the treatment of oral candidiasis has fluconazole. The use of fluconazole in the treatment of fungal infection Candida albicans is completely safe and patients treated with this drug showed a longer period without recurrence compared to patients treated with nystatin.